The Influence Of Management Accounting Information System Quality And Work Discipline On Employee Performance From An Islamic Economic Perspective (Study at the Department of Cooperatives, MSMEs and Industry, North Lampung) - Anggraeni, Septia; Ekawati, Evi; Devi, Yulistia (IAIN Kendari, 2024)
Performance is an individual thing, because each employee has a different level of ability in carrying out their duties. Performance depends on a combination of ability, effort and opportunities obtained. Performance is the result or output of a process. Then every employee can complete all workloads effectively and efficiently so that problems that occur in the organization can be resolved properly. This research uses quantitative methods. The sample used in this research was 49 employees.Meanwhile, the data collection technique used was a questionnaire. Data were processed using SPSS version 25. The independent variables in this research were the quality of the management accounting information system and work discipline and employee performance as the dependent variables. The research results based on the t- test showed that the quality of the management accounting information system has a significant effect on employee performance and work discipline has a significant effect on employee performance. The research results based on the F test showed that the quality of the management accounting information system and work discipline simultaneously have a significant effect on employee performance. The results of statistical testing show that there is an influence on the quality of the management accounting information system and employee work discipline from an Islamic economic perspective (study at the North Lampung Cooperatives, UMKM and Industrial Service).